Drosophila Tempura, a novel protein prenyltransferase α subunit, regulates notch signaling via Rab1 and Rab11. - Wu-Lin Charng (Public Library of Science (PLoS), 2014)
Vesicular trafficking plays a key role in tuning the activity of Notch signaling. Here, we describe a novel and conserved Rab geranylgeranyltransferase (RabGGT)-α-like subunit that is required for Notch signaling-mediated lateral inhibition and cell fate determination of external sensory organs. This protein is encoded by tempura, and its loss affects the secretion of Scabrous and Delta, two proteins required for proper Notch signaling. We show that Tempura forms a heretofore uncharacterized RabGGT complex that geranylgeranylates Rab1 and Rab11. This geranylgeranylation is required for their proper subcellular localization. A partial dysfunction of Rab1 affects Scabrous and Delta in the secretory pathway. In addition, a partial loss Rab11 affects trafficking of Delta. In summary, Tempura functions as a new geranylgeranyltransferase that regulates the subcellular localization of Rab1 and Rab11, which in turn regulate trafficking of Scabrous and Delta, thereby affecting Notch signaling.